F-doped nickel cobalt oxide-carbon composite electrocatalysts paired with mechanically robust anion-conducting chitosan membranes for flexible and rechargeable zinc-air batteries - Kurian, Maria; Ranganath, Suresha P.; Vijayakumar, Vidyanand; Sivadasan, Sneha; Kurian, Rachna Maria; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Energy Materials, 2024)
High-performing, cost-effective electrocatalysts and anion-conducting polymer electrolyte membranes are essential for realizing commercially affordable zinc-air batteries (ZABs). In this context, the present work deals with the development of a bifunctional electrocatalyst and an anion-exchange quasi-solid-state electrolyte membrane (based on quaternary ammonium group-grafted chitosan) for demonstrating flexible and rechargeable ZABs. The electrocatalyst composed of NiCoO2 nanoparticles supported on a carbon framework showcased substantial advancements in its ability to catalyze both oxygen reduction and evolution reactions (ORR and OER) due to the heteroatom doping by fluorine. For instance, the optimized electrocatalyst (F-NCO-ADC-600) exhibited an onset potential of 0.96 V vs RHE with a half-wave potential of 0.83 V vs RHE for ORR, a comparable performance with the state-of-the-art Pt/C (1.0 and 0.86 V vs RHE, respectively). On a similar note, the same catalyst also displayed an overpotential of 340 mV vs RHE for OER at a current density of 20 mA cm(-2), close to that of a standard RuO2 catalyst (337 mV vs RHE). In the context of polymer electrolytes, the quaternary ammonium-group-grafted chitosan membrane depicted superior ionic conductivity, liquid electrolyte uptake, and mechanical properties, thereby proving to be an efficient anion-conducting polymer electrolyte membrane. The realistic application of the developed electrocatalyst and the polymer electrolyte membrane is demonstrated in the ZAB prototypes. The assembled rechargeable ZAB (RZAB) delivered a power density of 207 mW cm(-2) and maintained high-rate capability and cycling stability, notably in a flexible configuration (f-RZABs). Thus, this work provides a strategy for the rational design of anion-exchange membranes and bifunctional electrocatalysts for f-RZABs.
Keywords: anion-conducting polymer electrolytemembrane; F-doping; flexible and rechargeable zinc-air batteries(f-RZABs); oxygen evolution reaction(OER); oxygen reduction reaction (ORR)